O papel da afetividade nas aulas de língua inglesa em dois diferentes contextos escolares: cognição e afetividade caminham juntas - Carreira, Paula Paques (2014)
This study aimed at understanding the role of affective aspects in the English Language teaching and learning process in two different contexts: regular school and language center. The theoretical background was based upon the studies about affectivity by Almeida (2002), Mahoney (2002), Leite (2002), Tassoni (2002), Rossini (2001), as well as studies on foreign language teaching and learning by Celani (2001), Duarte (2010), Almeida Filho (2010), Paiva (1999), Leffa (1988), and Arnold and Brown (1999). Qualitative research methodology was employed and the data collection instruments used were essay writing and questionnaire. The results indicate that the main role of affective aspects in English language teaching and learning is to enable students involvement with assigned activities, providing a pleasant relationship with the learning of a new language, because for the students that participated in this study English language teaching should be guided by pedagogic practices that engage them in their everyday issues, that foster good teacher student, student student interaction and gives them opportunities to travel, meet new people, a new culture, adding value to their personal and professional future. In short, the results hint that we should reflect on a pedagogical practice guided by students needs, learned as a whole and that furthers their development in affective, cognitive and motor aspects